2019
DOI: 10.1152/japplphysiol.00321.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-alanine supplementation during high-intensity interval training on repeated sprint ability performance and neuromuscular fatigue

Abstract: The study investigated the influence of β-alanine supplementation during a high-intensity interval training (HIIT) program on repeated sprint ability (RSA) performance. This study was randomized, double-blinded, and placebo controlled. Eighteen men performed an incremental running test until exhaustion (TINC) at baseline and followed by 4-wk HIIT (10 × 1-min runs 90% maximal TINC velocity [1-min recovery]). Then, participants were randomized into two groups and performed a 6-wk HIIT associated with supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
(66 reference statements)
3
21
0
Order By: Relevance
“…In accordance with the improvement in V̇O 2max results, we found a considerable increase in RSA performance of 9.2% after the 8-week self-paced HIIT intervention. In another study, supporting findings were observed for the RSA that, a 6-week HIIT training intervention induced a decrease by 1.5% their total time of RSA [ 41 ]. In another study, Cicioni-Kolsky et al [ 42 ] showed that the RSA test duration decreased from 36.0 ± 1.9 ml·min -1 ·kg -1 to 35.0 ± 1.3 ml·min -1 ·kg -1 with an increase of 3.7% after 6-week HIIT in recreationally and moderately trained young males.…”
Section: Discussionsupporting
confidence: 54%
“…In accordance with the improvement in V̇O 2max results, we found a considerable increase in RSA performance of 9.2% after the 8-week self-paced HIIT intervention. In another study, supporting findings were observed for the RSA that, a 6-week HIIT training intervention induced a decrease by 1.5% their total time of RSA [ 41 ]. In another study, Cicioni-Kolsky et al [ 42 ] showed that the RSA test duration decreased from 36.0 ± 1.9 ml·min -1 ·kg -1 to 35.0 ± 1.3 ml·min -1 ·kg -1 with an increase of 3.7% after 6-week HIIT in recreationally and moderately trained young males.…”
Section: Discussionsupporting
confidence: 54%
“…Increased H + production is partly buffered inside the muscle by carnosine ionic microdomains, which deposits H + /Ca 2+ in the cytoplasm to regulate intracellular pH, partly expelling the remaining H + to systemic blood [ 3 ]. Previous studies with trained cyclists performing time-trials [ 25 , 27 , 33 ] or after 1-h of moderate intensity cycling [ 34 ] did not observe a difference in lactate or blood pH by β-ala. On the other hand, athletes engaged in high-intensity interval training yielded higher lactate values compared to placebo after these efforts [ 35 , 36 ] in line with our results. However, the buffering capacity of muscles did not change in these studies in spite of an increased muscle carnosine, suggesting an improved muscle force in short-duration high-intensity movements by acting on neuromuscular fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…Participants performed two 5 s maximal voluntary contractions (MVCs) with the knee extensors of their self-reported dominant leg, interspersed with 1 min of passive rest [8,23,24]. The two MVCs were performed at baseline and as soon as possible after (77.50 ± 21.49 s) the RSA test.…”
Section: Force Data Acquisitionmentioning
confidence: 99%
“…The two MVCs were performed at baseline and as soon as possible after (77.50 ± 21.49 s) the RSA test. The measurements were carried out in a specific chair designed for maintaining hip and knee flexion at 90°, with participants secured by straps [8,23,24]. A metal rod was attached to the ankle and connected to a load cell with a maximum capacity of 100 kgf (MK Controle, São Paulo, SP, Brazil).…”
Section: Force Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation